Hepatopoietin Cn (HPPCn) Generates Protective Effects on Acute Liver Injury - Li, Na; Liu, Feng-Jiao; Li, Dan-Dan; Sun, Chun-Xia; Li, Jian; Qu, Mei-Hua; Cui, Chun-Ping; Zhang, Da-Jin (Frontiers in Pharmacology, 2019)
Objective To observe the protective role of HPPCn on acute liver injury. Methods Six hours after 10 mmo1/L CC14, 150 mmol/L ethanol or 0.6 mmol/L H2O2 treatment, SMMC7721 human hepatoma cells were incubated with 10, 100, and 200 ng/ml rhHPPCn for an additional 24 hours. The cell survival rate was analyzed by a CCK-8 assay. The CC14-induced apoptosis of SMMC7721 cells was detected by flow cytometry. Then, the levels of GOT, GPT, MDA, LDH, GSH-PX and SOD in SMMC7721 cell lysates and cell culture supernatants were detected. SMMC7721 cells were treated with different concentrations of rhHPPCn (0, 10, and 100 ng/ml). The expression of cell proliferation indexes (BrdU and PCNA) was detected by IHC. An acute liver injury mouse model was established by a one-time tail vein injection of 20% CCL4 at a volume of 5 ml/kg body weight. One hour after the injection, 2.5 mg rhHPPCn/12 h/kg body weight was administered through a tail vein injection. The serum levels of GOT and GPT were detected, and pathological changes in the liver were evaluated. The expression changes of PCNA were observed by IHC. Results rhHPPCn increased the survival rate of SMMC7721 cells and inhibited chemical toxicity-induced cell apoptosis. The levels of GOT, GPT, MDA, and LDH in the cell supernatant were significantly reduced, while GSH-PX and SOD levels were significantly increased after rhHPPCn treatment in the CCl4-treated SMMC7721 cells. The expression of BrdU and PCNA was increased in a concentration-dependent manner, indicating that rhHPPCn promotes cell proliferation. In addition, rhHPPCn has a liver-protective effect against liver injuries in vivo. rhHPPCn significantly reduced serum GOT and GPT levels in mice with CCl4-induced acute liver injury in a time- and concentration-dependent manner and significantly increased the expression of PCNA in the liver. Conclusion rhHPPCn protects hepatocytes from chemical agents by promoting proliferation and inhibiting apoptosis both in vivo and in vitro. Our study provides new insights for the clinical treatment of acute liver injury.